Experimental study on rock mechanical response during CO2injection into limestone reservoir at different conditions - Zhang, Y.; Lebedev, Maxim; Sarmadivaleh, Mohammad; Barifcani, Ahmed; Iglauer, Stefan (2018)
Copyright © 2018 ARMA, American Rock Mechanics Association. CO2 storage in deep saline aquifers is the green technology to mitigate climate change by greenhouse gas emissions. The carbonate reservoir such as limestone is the popular storage site due to widely existed. However, such reservoirs are sensitive to the acidic CO2 fluids and how the geomechanical response for different areas in the storage sites are poorly understand. Thus in this paper, we measured the geomechanical response on Savonnières Limestone samples by UCS test on three different reservoir conditions: near the wellbore – scCO2 flooding, distances with wellbore – CO2 saturated brine flooding, and far from the wellbore – dead brine saturated. The flooding tests were set as a representative reservoir conditions at approximately 1000m depth with 325 K/50oC, 15 MPa confining pressure and 10 MPa pore pressure. The results show that the CO2 saturated brine flooding had largest dissolution effect with lowest maxim unconfined compressive stresses. We thus concluded that the most matrix damaged area by acid fluid dissolution should be some distances around the wellbore but not near the wellbore, and such geomechanical weakening may cause potential geohazard such as layer collapse and fault reactive.